$a)$ Để $~\dfrac{2}{x-1}$ có giá trị nguyên thì $2~\vdots x-1$
$\rightarrow x-1\in Ư(2) = \left\{-2;-1;1;2 \right\}$
$\rightarrow x \in \left\{-1;0;2;3 \right\}$
$b)$ Để $~\dfrac{x+3}{x+2}$ có giá trị nguyên thì:
$x + 3~\vdots x+2$
$\rightarrow (x+2) +1~\vdots x + 2$
$\rightarrow 1~\vdots x + 2$
$\rightarrow x+2\in Ư(1) = \left\{-1;1\right\}$
$\rightarrow x \in \left\{-3; -1 \right\}$
$c)$ Để $~\dfrac{2x+1}{x-1}$ có giá trị nguyên thì:
$2x+1~\vdots x-1$
$\rightarrow (2x-2)+3~\vdots x-1$
$\rightarrow 2(x-1) +3~\vdots x - 1$
$\rightarrow 3~\vdots x-1$ (vì $2(x+2)~\vdots x -1$)
$\rightarrow x-1\in Ư(3) = \left\{-3;-1;1;3\right\}$
$\rightarrow x \in \left\{-2;0;2;4 \right\}$